Negative Representative & Expressive Act in Trump’s Dominance on The United States Presidential Debate 2020 “Covid-19 Issue” - Misyi Gusthini; Lia Maulia Indrayani; Rosaria Mita Amalia; Elvi Citraresmana (Intermestic: Journal of International Studies, 2022)
This article analyze the use of representative and negative expressive speech acts on the dominance of Trump's utterances in the final debate of the first United States president against Joe Biden. The data is a video transcript of the United States presidential candidate debate in September 2020, specifically the debate on the Covid-19 motion. This study focuses on the dominance of Trump's utterances which have negative expressive and representative meanings. Using a qualitative descriptive method, the writer applies Yule's theory of speech acts and Fairclough's theory of language and power, to analyze dominance based on content, relations, and subject matter. The results show that in the domination of Trump's utterances there are three negative representative datas with the function of bragging about performance results in handling the pandemic and two negative expressive datas which also have the function of boasting and pitying Biden's ignorance of several Covid-19 situations in 2020.